Model Pembelajaran Treffinger: Pengaruh Penerapan terhadap Hasil Belajar Fisika Materi Kalor - Eka Syiam Sholekhah; Siti Anisatur Rofiqah; Effendi Effendi (U-Teach: Journal Education of Young Physics Teacher, 2020)
The purpose of this study was to determine the effect of the application of the Treffinger learning model on student physics learning outcomes on heat topic in class VII SMP NU Tebat Jaya in the 2019/2020 school year. This research was an experimental research design with Posttest Only Control Group Design. The samples of this research were 28 students of class VII A and 28 students of VII B. The data collection method in this study was a multiple-choice test method. The data analysis used was a statistical test using the t test statistical formula. Based on data analysis using the t-test, it was concluded that there was a significant effect of the application of the Treffinger learning model on students' physics learning outcomes on heat topic in class VII SMP NU Tebat Jaya in the 2019/2020 learning year with tcount 5.45 and ttable 1, 99.